Analysis by gas chromatography-mass spectrometry of the volatile components of Teucrium lusitanicum and Teucrium algarbiensis - Cavaleiro, C. (2015)
The essential oils from four samples of Teucrium lusitanicum and one sample of Teucrium algarbiensis, grown in Algarve (southern Portugal) were analyzed by gas chromatography (GC) and gas chromatography-mass spectroscopy (GC-MS). Seventy-one volatile compounds were identified. Major compounds of T. algarbiensis oil were alpha-pinene (8.3%), sabinene (7.2%), beta-pinene (10.2%), limonene (11.8%) and germacrene D (7.6%). Concerning T. lusitanicum, some quantitative differences were found with regards to the major constituents of the oils from four populations: alpha-pinene (0.8-8.5%), sabinene (2.1-9.6%), beta-pinene (2.5-11.9%), limonene (1.2-11.5%) and elemol (2.6-12.0%). (C) 2004 Elsevier B.V. All rights reserved.